KONFLIK KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. PARKLAND WORLD INDONESIA PLANT 2 BAGIAN STOCKFIT CELL 5 KABUPATEN SERANG-BANTEN - Santi Santi; Ende Ende; Riza Wijayanti (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
The Company is required to have a reliable employee performance, at PT. Parkland World Indonesia 2, especially Stockfit Cell 5, has some obstacles in achieving the company's target due to the lack of focus of employees while working, causing a decrease in employee performance. This research aims to determine the influence of work conflicts and work environment on employee performance at PT. Parkland World Indonesia Plant 2 Serang-Banten. The research method used is Quantitative. With a population of 50 employees and a sample of 50, using saturated techniques, with the spread of questionnaires to 50 respondents employees at PT. Parkland World Indonesia 2 Serang-Banten. Based on the analysis of the study obtained the calculation value in the form of a coefficient of determination (R2 ) has a value of 66.6% which contributes enough in attachment to the influence between free variables against bound variables. T test result is variable work conflict obtained tcount value 7,002 > 2,010 ttable and work environment obtained tcount value of 4,354 > 2,010 ttable and signification value less than 0.05.The results of the study simultaneously obtained the results of Fcount of 46,844 > Ftable of 2,804. Based on the results of the study, it can be concluded that the relationship between work conflict variables and work environment variables partially and simultaneously to employee performance has a positive influence even very significant